Influence of FGF23 and Klotho on male reproduction: Systemic vs direct effects. Issue 9 (30th July 2020) - Bøllehuus Hansen, Lasse; Kaludjerovic, Jovana; Nielsen, John Erik; Rehfeld, Anders; Poulsen, Nadia Nicholine; Ide, Noriko; Skakkebaek, Niels Erik; Frederiksen, Hanne; Juul, Anders; Lanske, Beate; Blomberg Jensen, Martin
Abstract: Currently, no treatment exists to improve semen quality in most infertile men. Here, we demonstrate systemic and direct effects of Fibroblast growth factor 23 (FGF23) and Klotho, which normally regulate vitamin D and mineral homeostasis, on testicular function. Direct effects are plausible because KLOTHO is expressed in both germ cells and spermatozoa and forms with FGFR1 a specific receptor for the bone‐derived hormone FGF23. Treatment with FGF23 increased testicular weight in wild‐type mice, while mice with global loss of either FGF23 or Klotho had low testicular weight, reduced sperm count, and sperm motility. Mice with germ cell‐specific Klotho (gcKL) deficiency neither had a change in sperm count nor sperm motility. However, a tendency toward fewer pregnancies was detected, and significantly fewer Klotho heterozygous pups originated from gcKL knockdown mice than would be expected by mendelian inheritance. Moreover, gcKL mice had a molecular phenotype with higher testicular expression of Slc34a2 and Trpv5 than wild‐type littermates, which suggests a regulatory role for testicular phosphate and calcium homeostasis. KLOTHO and FGFR1 were also expressed in human germ cells and spermatozoa, and FGF23 treatment augmented the calcium response to progesterone in human spermatozoa. Moreover, cross‐sectional data revealed that infertile men with the highest serum Klotho levels had significantly higher serum Inhibin B and total sperm count than men with the lowest serum Klotho concentrations. In conclusion, this translational study suggests that FGF23 and Klotho influence gonadal function and testicular mineral ion homeostasis both directly and indirectly through systemic changes in vitamin D and mineral homeostasis.